TINJAUAN YURIDIS TERHADAP KASUS PENGGUNAAN DEEPFAKE PADA DOKTER DALAM PERIKLANAN OBAT-OBATAN DI INDONESIA: Juridicial Review of Deepfake Usage Involving Doctors in Medicine Advertising in Indonesia - Faiz Ahmad Fachri; Zhairah Zulaeyka Imran; Feni Febriani; Nahyashifa Ramadhani Kadir Al-Yafie; Nurul Aini Japar (Fakultas Hukum Universitas Komputer Indonesia, 2026)
The rapid advancement of Artificial Intelligence (AI) technology, particularly deepfake, has triggered a significant escalation in cybercrime. An alarming trend is the unauthorized manipulation of doctors' biometric identities to promote illegal drugs, which severely threatens public health and damages professional medical reputations. This research aims to analyze existing legal policies and formulate robust protections for doctors victimized by such biometric manipulation. Utilizing a normative legal research method, this study applies statutory, conceptual, and comparative approaches. The findings reveal that while Indonesia's Electronic Information and Transactions (ITE) Law and Personal Data Protection (PDP) Law provide a basis for prosecution, the PDP Law offers a more precise framework under the Lex Systematische Specialiteit principle concerning biometric data. Current repressive measures include criminal prosecution and the